Fractional excretion of tumor necrosis factor receptor 1 and 2 in patients with type 2 diabetes and normal renal function. Issue 3 (10th August 2020) - Gohda, Tomohito; Kamei, Nozomu; Kubota, Mitsunobu; Tanaka, Kanako; Yamashita, Yoshinori; Sakuma, Hiroko; Kishida, Chiaki; Adachi, Eri; Koshida, Takeo; Murakoshi, Maki; Hagiwara, Shinji; Funabiki, Kazuhiko; et al.
Abstract: Aims/Introduction: Increased concentrations of serum tumor necrosis factor (TNF) receptors (TNFRs; TNFR1 and TNFR2) are positively associated with the urinary albumin‐to‐creatinine ratio (ACR), and negatively associated with the estimated glomerular filtration rate (eGFR) in patients with type 2 diabetes. However, the mechanism underlying this increase and the relationship between TNFRs in serum, and urine and kidney measures (ACR and eGFR) are unclear. Materials and Methods: This was a cross‐sectional study that included 499 patients with type 2 diabetes and eGFR ≥60 mL/min/1.73 m 2 . The concentrations of TNFRs in serum and urine, and their respective fractional excretion, were measured. Results: Serum and urinary TNFR levels were positively associated with the ACR, and negatively associated with the eGFR. The fractional excretion of TNFRs did not differ between patients with an eGFR ≥90 and those with an eGFR 60–89 mL/min/1.73 m 2, and also did not correlate with eGFR. After adjustment for relevant covariates, the serum TNFRs were associated with a lower eGFR (60–89 mL/min/1.73 m 2 ) and an increased ACR (≥30 mg/gCr), but urinary TNFRs were associated with an increased ACR (≥30 mg/gCr) alone, in the multivariate logistic model. Conclusions: The pattern of fractional excretion TNFRs showed that an increase in serum TNFRs might result from their increased systemic production, including in the kidney, rather than being a simple reflection of GFR decline. Kidney measures appear to be strongly associated with serum TNFRs rather than urinary TNFRs in patients with type 2 diabetes and normal renal function. Abstract : A scatter plot of the relationship between fractional excretion tumor necrosis factor receptors (TNFR) and serum or urinary TNFR levels showed that urinary TNFR levels are strongly associated with fractional excretion TNFR levels. However, serum TNFR levels are not strongly associated with fractional excretion TNFR levels.